2022
DOI: 10.3390/nano12132275
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Calcium Carbonate Nanoparticles on the Soil Burial Degradation of Polybutyleneadipate-Co-Butylenetherephthalate Films

Abstract: A polybutyleneadipate-co-butylenetherephthalate (PBAT) sample, commercially known as Ecoflex®, was processed via melt extrusion with CaCO3 nanoparticles coated with a hydrophobic coating. Blown films of PBAT and two composites with nanofiller (2% and 5%wt) were prepared and degradation tests in soil at 30 °C up to 180 days were carried out with weight loss measurements. Furthermore, biodegradation test according to ISO 14851 was carried out at 30 °C. The effect of CaCO3 on soil burial degradation was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…(2019) observed a degradation rate of 18.4% for PBAT films (1*1 cm 2 ) in soils at 28°C over 182 days, while Rapisarda et al. (2022) observed PBAT films (2*2 cm 2 ) degradation rate of 4.6% after 90 days of biodegradation at 30°C. Meanwhile, PLA (pellets) exhibited a degradation level of approximately 16% over 180 days at a controlled temperature of 25 ± 2°C (Palsikowski et al., 2018).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…(2019) observed a degradation rate of 18.4% for PBAT films (1*1 cm 2 ) in soils at 28°C over 182 days, while Rapisarda et al. (2022) observed PBAT films (2*2 cm 2 ) degradation rate of 4.6% after 90 days of biodegradation at 30°C. Meanwhile, PLA (pellets) exhibited a degradation level of approximately 16% over 180 days at a controlled temperature of 25 ± 2°C (Palsikowski et al., 2018).…”
Section: Resultsmentioning
confidence: 98%
“…In a comprehensive study on the biodegradation of different biodegradable plastics, PBAT (2 mm film) exhibited variable degradation rates after 120 days of exposure to various soil types at a temperature of 30°C in darkness, ranging from 0.3 to 16% (Han et al, 2021). Souza et al (2019) observed a degradation rate of 18.4% for PBAT films (1*1 cm 2 ) in soils at 28°C over 182 days, while Rapisarda et al (2022) observed PBAT films (2*2 cm 2 ) degradation rate of 4.6% after 90 days of biodegradation at 30°C. Meanwhile, PLA (pellets) exhibited a degradation level of approximately 16% over 180 days at a controlled temperature of 25 ± 2°C (Palsikowski et al, 2018).…”
Section: Co 2 Effluxmentioning
confidence: 99%
“…Biocomposites were unearthed after established intervals (10 and 30 days), brushed gently, cleaned with distilled water numerous times, and dried at room temperature, in the presence of P 2 O 5 , under vacuum to constant weight. 42 The degree of degradation was estimated by WL by the Equation ( 1):…”
Section: Compost Burial Testmentioning
confidence: 99%
“…poly(LO-alt-PA) possesses substituent groups that limit accessibility to ester groups, on whose hydrolysis the degradation of the tested polymeric materials depends. Because biodegradability is one of the properties of these polymers, biodegradability tests were performed according to ISO standard 14851 [36] with the respirometric BOD (biochemical oxygen demand) method [39]. Figure 6 shows the average percentage of biodegradation plotted as a function of time for LOPA 08, LOPA 10, and the positive reference (microcrystalline cellulose).…”
Section: Catalystmentioning
confidence: 99%